Firm performance in times of crisis: does an innovative business strategy matter? - Haque, Md Reiazul; Inam, Aneeq; Mehanna, Rock-Antoine; Mia, Parvez (Journal of Business Economics and Management, 2025)
This study examines whether a firm’s business strategy – innovative vs. conservative – determines the extent to which a crisis impacts its performance. To explore this, the study calculates business strategy scores as a composite measure of six variables, where a high (low) score indicates an innovative/prospective (conservative/defensive) strategy. The COVID-19 pandemic (2020–2021) serves as the crisis context for the analysis. Using a sample of 7,143 firm-year observations in the U.S., the study finds that while the sample firms experienced a decline in their performance during the COVID-19 crisis period compared to the pre-crisis level (2018–2019), the decline was less pronounced for firms following innovative strategies. This finding suggests that a firm’s business strategy is a crucial determinant of its performance during a crisis. The study enhances theoretical understanding that business strategy is particularly important when operating conditions are abnormal.